KOMUNIKASI PENYULUHAN MANGGALA AGNI DALAM MEMBINA MASYARAKAT PEDULI API (MPA) DI DESA SUNGAI RAWA KABUPATEN SIAK - Duike Friscalia; Rusmadi Auza (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Forest fire prevention activities and land on peatlands is a step in the activities conducted focus seeks to prevent forest fires and land, not the activity for the treatment of land and forest fires. When prevention has been attempted with the maximum then no handling activities of forest fire because there is no more land and forest fires in peatlands caused by human action both intentional and unintentional. Forest fires through training programs to increase the capacity of empowerment of Concerned Citizens Fire (MPA) is expected to address land and forest fires is going well.The method used in this study is a qualitative research method with descriptive approach, trying to describe or illustrate how communication counseling in the process of formation of Concerned Citizens Fire by Manggala Agni in Riau Province has the largest peatland and centered in the village of Rawa Sungai Siak. Data was collected through interviews, observation and documentation. Data analysis techniques include data reduction, data presentation and conclusion and verification.These results indicate that the realization of Concerned Citizens independent of Fire, where the MPA Sungai Rawa able to plan and implement social control over land and the environment. Implementation of fire prevention activities are under the district government as the implementing unit is Manggala Agni Siak. The timing of the activity of maximum extension for two years, after which the district government or the parties may provide synchronization control programs and the prevention of forest fires or rewards the Community Care Team Fire (MPA) is. Monitoring and evaluation of the program conducted by the relevant stakeholders through field visits and reporting.Keywords : Communication Extension , Forest Fire , Mangala Agni, Community Care Fire (Masyarakat Peduli Api)